2021
DOI: 10.1111/jpm.12778
|View full text |Cite
|
Sign up to set email alerts
|

What are the ethical dilemmas in the decision‐making processes of nursing people given electroconvulsive therapy? A critical realist review of qualitative evidence

Abstract: Accessible Summary What is known on the subject? ECT is a treatment which has a long and complicated history. There is no consensus on its effectiveness and there is a great deal of polarized debate as to whether it should be used. MHNs are asked to work with people who are receiving ECT as part of their duties. What the paper adds to existing knowledge? The paper seeks to move beyond the polarized arguments and to consider how MHNs can work with people where ECT is being considered or administered as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…40% ( n = 37) of the realist reviews cited use of an advisory group at some stage (as per the working definition for this study, notably other terminology was often reported) [14–17, 25–61]. 60% ( n = 56) did not mention the use of an advisory group [62–117]. Of those that did not mention an advisory group, seven reviews [62–64] did report participant involvement that did not fulfill the criteria of an advisory group, i.e., participants were used as data sources but did not advise on the review.…”
Section: Resultsmentioning
confidence: 99%
“…40% ( n = 37) of the realist reviews cited use of an advisory group at some stage (as per the working definition for this study, notably other terminology was often reported) [14–17, 25–61]. 60% ( n = 56) did not mention the use of an advisory group [62–117]. Of those that did not mention an advisory group, seven reviews [62–64] did report participant involvement that did not fulfill the criteria of an advisory group, i.e., participants were used as data sources but did not advise on the review.…”
Section: Resultsmentioning
confidence: 99%
“…This includes the right to choose or refuse treatment and respect for an individual's autonomy. Based on current evidence, and considering the manifest risks versus benefits of ECT, mental health nurses need to critically evaluate their role in this psychiatric practice, all the while ensuring they are acting in the best interests of individuals in their care (Sweetmore, 2022). This may require them to consider the language, content, accuracy, lens and balance of any information provided about ECT.…”
Section: R Eleva Nc E For C Li N Ica L Pr Ac T Ic Ementioning
confidence: 99%